Changes in the Prevalence of Self-Harm in Adolescents after the First Wave of COVID-19 (Journal of Advanced Research in Social Sciences, 2022)
As a consequence of the COVID-19 pandemic and the restrictions aimed at reducing its impact, mental health experts have reported an increased occurrence of mental health issues and disorders. This might be especially true for the adolescent population, since social contact with peers and education is crucial for the healthy mental development of this age group. Out of all of the age groups, the isolation that resulted from the lockdowns was most intensely felt by adolescents. The presented study focuses on the impact of the first wave of the pandemic on the prevalence and intensity of self-harming behaviour. Two groups of adolescents were included in the research (a group studied prior to the outbreak of the pandemic and a group studied after the first wave of the pandemic), which were similar in terms of age and gender distribution. The comparative analysis of the level of self-harm using a modified Self-Harm Inventory did not reveal an increased prevalence of self-harming behaviour among adolescents after the first wave of the pandemic compared to the pre-pandemic state.